Estrus detection methods in dairy cattle and conception rate (Research, Society and Development, 2024)
Given the importance of dairy farming on the national background, understanding the productive efficiency of the herd is essential. However, estrus detection is still considered a challenge, so the inclusion of efficient detection methods has become increasingly necessary. Thus, the objective of the study was to identify, in three dairy farms, the estrus detection methods that have been adopted by the establishments, as well as to estimate the conception rates in these locations. The study was conducted on three farms in the southeast region, and for each farm a different detection method was adopted (Estrotect, Visual or Identification collar). The factors associated with the conception rate and which aspects could influence these values were evaluated. It can be concluded that visual detection was the least efficient, with a service rate of 58.76%. The electronic detection method (use of an identification necklace) proved to be more satisfactory when compared to the other ones, achieving a service rate of 78.17%. Therefore, given the importance of dairy farming in the national scenario and the need to find alternative and efficient ways to detect estrus, such as the use of electronic equipment, as demonstrated in the present research, studies in this area should be carried out considering a greater sample number so that, in fact, technologies can be identified and contribute to increasingly better results.